Characterization of key aroma-active compounds in Hanyuan Zanthoxylum bungeanum by GC-O-MS and switchable GC × GC-O-MS. (15th August 2022) - Zhao, Mu; Li, Ting; Yang, Fan; Cui, Xinyue; Zou, Tingting; Song, Huanlu; Liu, Ye
Highlights: The aroma compounds in Hanyuan Zanthoxylum bungeanum were identified by GC × GC-O-MS. 72 volatile compounds were identified by GC-O-MS, of which 28 were aroma-active. 116 volatile compounds were identified by GC × GC-O-MS, 43 of which were aroma-active. 23 important aroma-active compounds with FD ≥ 27 were identified by AEDA. Compounds were quantified by external standard curves and OAV. Abstract: The present study sought to characterize the composition of volatile aroma compounds and key aroma-active compounds of dried Hanyuan Zanthoxylum bungeanum . The volatile aroma compounds were analyzed by the solid-phase microextraction (SPME) combined with gas chromatography–olfactometry-mass spectrometry (GC-O-MS) and two-dimensional comprehensive gas chromatography–olfactometry-mass spectrometry (GC × GC-O-MS). The key aroma-active compounds were analyzed by the aroma extract dilution analysis and odor activity value. A total of 72 volatile compounds were identified by GC-O-MS, of which 28 were aroma-active. Meanwhile, 116 volatile compounds were identified by GC × GC-O-MS, of which 43 were aroma-active. These results revealed that myrcene, (+)-limonene, (E) - β -ocimene, β -cubebene, Germacrene D, cineole, linalool, and linalyl acetate were the key aroma-active compounds of dried Hanyuan Zanthoxylum bungeanum .